Effects of plastic mulch color on melon production: two cycles - Hernández-Pérez , Armando; Torres-Olivar, Vicente; García-Santiago, Juana Cruz; Ibarra-Jiménez, Luis (Ecosistemas y Recursos Agropecuarios, 2021)
The objective of the present study was to determine the effect of plastic mulches on soil temperature, growth, yield, photosynthesis and stomatal conductance of the melon crop in two cycles. The assessed treatments were: blue plastic mulch (APA), black plastic mulch (APN), aluminum plastic mulch (APL), white plastic mulch (APB) and soil without mulch (Control). In the second cycle the APL was replaced by red plastic mulch (APR). The results showed that the soil temperature was higher in the APA, APN and APR. The dry biomass was higher in the APA, APN and APL; while, the leaf area and yield were similar in the different mulch colors in the two evaluated cycles. The net photosynthesis and stomatal conductance were affected by mulch color at 45 and 60 days after sowing (dds).